THE ROLE AND UNIQUE STYLE OF THE WORK “TAWILAT AHL AL-SUNNAH” IN THE TRADITIONS OF TAFSIR (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the unique style of interpretation in Abū Manṣūr al-Māturīdī's work “Ṭāwilāt ahl al-Sunnah”. The commentator uses narration and reason in harmony, and sheds light on issues of faith with an analytical approach. The work demonstrates a high scientific style, based on the beliefs of Ahl al-Sunnah and relying on refutation, interpretation, and logic.